Peran Damkar Dalam Pelayanan Kepada Masyarakat - Siahaan, Rumiris; Purba, Rakhmawati; Batubara, Rizki Wulanita; Marpaung, Josua; Sofyan, Mhd. Hafiq; Fahlevi, Mhd. Aswad; Pradytia, Adji Arifanda; Afifi, Dinda Nora Putri; Nainggolan, Pinondang (Community Service Progress, 2024)
Fire is a disaster that can result in huge losses and these fire disasters often occur in the middle of residential areas regardless of time, status or even distance. The city of Tebing Tinggi is prone to fire disasters, with fires almost every month. Internship is a student activity given in the final semester of study. Useful for training students to know the world of work. Placing internship students in the Fire Department is useful so that they can help communities experiencing disasters by going through the preparation, implementation and evaluation stages. The results of this internship provide benefits for both the campus and the Tebing Tinggi city fire department. There is good cooperation between the two institutions.